Temple groups of the Hanuman Garhi temple complex - Temples of India Project Team (Jio Institute, 2024)
Seen here are all the extant structures from the Hanuman Garhi temple complex. Starting from the left, one can see the gateway that must have been the original entrance of this temple complex, followed by several small shrines. The seventh shrine, seen towards the centre, has a shikhara (superstructure) in brick, likely added at a later date than the original construction. These are followed by three important structures from the complex, a ruined Shiva Temple, a Devi Temple, which is locally known as Chaunsath Yogini Temple, and the Neelkanth Mahadev Temple. In the foreground of all these structures is the kunda (water tank). The Neelkanth Mahadev Temple is the largest in this complex. This temple is likely to be dedicated to Lakulisha worship.